2014
DOI: 10.1002/jbmr.2246
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight Is Not Associated With Risk of Fracture: Results From Two Swedish Cohort Studies

Abstract: Development and growth in utero has been suggested to influence bone health. However, the relationship with risk of fracture in old age is largely unknown. Using Cox proportional hazards regression, we studied the association between birth weight and fractures at ages 50-94 among 10,893 men and women (48% women) from the Uppsala Birth Cohort Study (UBCoS, born 1915-29) and 1334 men from the Uppsala Longitudinal Study of Adult Men (ULSAM, born 1920-24). Measured birth weight was collected from hospital or midw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…(25,26) Further, bone structure demonstrates sexual dimorphism across the life course(27) and differences between the sexes are apparent already in newborn babies, females having smaller vertebral bodies than men even when adjusted for body size. (28) Our findings are in agreement with previous studies,(1315) in which no associations between body size at birth and hip fractures in either sex were observed. Greater body size at birth has been found to predict higher bone mineral density(79) and more robust bone structure(10) in older age, which could, in theory, lead to lower risk of hip fractures.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…(25,26) Further, bone structure demonstrates sexual dimorphism across the life course(27) and differences between the sexes are apparent already in newborn babies, females having smaller vertebral bodies than men even when adjusted for body size. (28) Our findings are in agreement with previous studies,(1315) in which no associations between body size at birth and hip fractures in either sex were observed. Greater body size at birth has been found to predict higher bone mineral density(79) and more robust bone structure(10) in older age, which could, in theory, lead to lower risk of hip fractures.…”
Section: Discussionsupporting
confidence: 93%
“…They have found no associations between body size at birth and fractures in later life. (1315) However, one previous study including men and women from the Helsinki Birth Cohort Study (HBCS) born 1924-1933 with follow-up up to 70 years showed that children with poorest height or weight gain during the school years (7-15 yrs.) were more likely to sustain hip fractures than those with highest gain.…”
Section: Introductionmentioning
confidence: 99%
“…Birth weight for example seems important for peak BMC [44], even though a Swedish study could not find any association to adult fracture risk in a cohort of women and men born in the year 1915–1929 [45]. Nationwide birth weight data for the birth cohorts in our study are not available for Sweden or Denmark.…”
Section: Discussionmentioning
confidence: 99%
“…Clues that osteoporosis may result from perturbations in the fetal programming of skeletal growth come from some, but not all, epidemiological data showing a relationship between low birth weight and future risk for lower bone mass and fragility fractures. 25 The importance of the fetal environment to skeletal development is further supported by reports that maternal smoking, nutrition and physical activity are linked to bone mass of the offspring at birth, 6 and that placental volume and morphology are associated with neonatal bone size and mineral content. 7 …”
mentioning
confidence: 93%